Strategic learning applied to technological Environments - Christen Muñiz, Ana Teresa (2017)
Technology is an essential element in our lives and in the same way it must be present in the educational field. In this regard, it is vital that the teacher updates his/her knowledge and guide his/her students in the best possible wayin the educational process. The present article concerns the need for teachers to generate a complex change in the way of teaching. The students can manage to consolidate knowledge and not only accumulate information throughspecialized web pages, tutorials and Wikis.